Konsep Pendidikan Karakter dan Adab: Pemikiran Adian Husaini - Radino Radino; Yunus Nur Hidayat (Nusantara: Jurnal Pendidikan Indonesia, 2022)
Character education in Indonesia is now experiencing a decline, thus proving that the government's efforts have not been successful in significantly improving the nation's character. So this requires the whole community, especially the leaders of Indonesian education observers to think of steps or solutions that are solutions to these problems. One of the figures who intensively gives criticism and suggestions for solutions for Indonesian education is Adian Husaini, he pays great attention to the problem of the nation's character. This study aims to describe the concept of character education from the perspective of Adian Husaini and its relevance to Islamic religious education. This research is a literature study, using the documentation method, while the data analysis uses descriptive qualitative analysis. The results of this study indicate that character education alone is not enough, character education should be balanced with adab education based on Islam which is relevant to the philosophy of the Indonesian nation which is based on the One Godhead. A curriculum based on adab cultivation and a piety curriculum is one of the alternative solutions that Adian Husaini has explained.